Maternal Mortality and Associated Factors in a Tertiary Care Center of Western Nepal - Shrestha, Junu; Gurung, Sangeeta; Shrestha, Ashika; Subedi, Anjali (Journal of Lumbini Medical College, 2017)
Introduction: Identifying the cause of maternal death is important. The aim of this study was to determine the causes of maternal deaths and the factors associated with it. Methods: This was an observational, cross-sectional, analytical study conducted at Department of Obstetrics and Gynecology, Manipal Teaching Hospital from July 2013 to June 2017. Women who died during pregnancy, delivery, or puerperium were included in the study. Demographic factors, clinical profile, cause and type of maternal deaths were noted by taking history and by inquiring with the medical personnel involved in managing patients. Data analysis was done using SPSS version 16. Results: There were 15 maternal deaths and 9923 livebirths. The maternal mortality ratio was 151 per 100,000 live births. Mean age of mothers was 28 years (SD = 7.5). Most of them were from rural areas, had low educational status. The mean gestational age at time of death was 33 weeks (SD = 7.5). Most of deaths (73%, n = 11) occurred in the postnatal period and 60% (n = 9) were critical at presentation. Direct obstetric causes like eclampsia was the most common (26.7%, n = 4) direct obstetric cause and cardiac disease was one of the important indirect cause (13.3%, n = 2). Delay in seeking health care and delay in reaching health center was the major reason for maternal deaths. Conclusion: Maternal mortality were mostly associated with direct obstetric causes, eclampsia being the most common. Most of the deaths were associated with delay in seeking health care and reaching health care centers.